Kontrol Amerika Serikat terhadap Private Military & Security Companies (PMSC) di Irak pasca Insiden Nisour Square 2007 - Pradnyana, I Putu Hadi; Fasisaka, Idin; Kumala Dewi, Putu Ratih (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2018)
ABSTRACT United States involves Private Military & Security (PMSC) in large numbers of Iraq reconstruction missions since 2004. The existence of PMSC actually cause problems. Violations such as shootings, violence, murder, and rape of Iraqi civilians are often perpetrated by US PMSC personnel. In September 2007 there was a shooting incident of PMSC personnel and left 17 Iraqi civilians dead and 24 wounded. This incident is called the Nisour Square. Great attention came from all over to condemn the actions of the US PMSC personnel. This seems to be a whip for the US to immediately make improvements. The basic indicator of violations by PMSCs in Iraq is the lack of control mechanisms. This study discusses comprehensively the US control measures post-incident Nisour Square 2007. The explanation is based on the concept of coercive isomorphism with three parts of adjustment; categorical & structural adjustments, procedural adjustments, and personnel adjustments. Keywords: Private Military & Security Companies (PMSC), Iraq reconstruction, control mechanism.